25‐2: Wide Color Gamut Display Based on Ultrastable Perovskite ‐ Polymer Film and Red QDs/Phosphors. Issue 1 (May 2017) - He, Juan; Chen, Haiwei; Chen, Hao; Wang, Yanan; Wu, Shin-Tson; Dong, Yajie
Abstract : We demonstrate a series of LCD backlight units with blue LED, green perovskite, and red Cd‐quantum dot or phosphors (Sr[LiAl3 N4 ]:Eu 2+ and Mn 4+ activated KSF). The central wavelength of our ultrastable, highly luminescent MAPbBr3 organic‐inorganic perovskite‐polymer film is 530 nm and FWHM ≈18nm. The obtained color gamut is ~90% Rec.2020 without Gaussian fitting.